2014
DOI: 10.1016/j.msec.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Understanding anisotropy and architecture in ice-templated biopolymer scaffolds

Abstract: Biopolymer scaffolds have great therapeutic potential within tissue engineering due to their large interconnected porosity and biocompatibility. Using an ice-templated technique, where collagen is concentrated into a porous network by ice nucleation and growth, scaffolds with anisotropic pore architecture can be created, mimicking natural tissues like cardiac muscle and bone. This paper describes a systematic set of experiments undertaken to understand the effect of local temperatures on architecture in ice-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 31 publications
3
84
3
Order By: Relevance
“…It has already been observed that the nucleation temperature has a huge impact on scaffold structure, as it is chiefly responsible for whether scaffolds are isotropic or anisotropic [5,7]. However, this study found no correlation between nucleation temperature and the final pore size at the top of the scaffold.…”
Section: Relationship Between Pore Structure and Thermal Parameterscontrasting
confidence: 77%
See 3 more Smart Citations
“…It has already been observed that the nucleation temperature has a huge impact on scaffold structure, as it is chiefly responsible for whether scaffolds are isotropic or anisotropic [5,7]. However, this study found no correlation between nucleation temperature and the final pore size at the top of the scaffold.…”
Section: Relationship Between Pore Structure and Thermal Parameterscontrasting
confidence: 77%
“…As the goal of this study was to link the pore size of isotropic scaffolds to a single thermal parameter, regardless of processing conditions, data were pooled from a previous study to evaluate the fit of the curve [7,17]. It was found that of all the thermal parameters tested, the time at equilibrium had the strongest relationship to pore size (figure 7).…”
Section: Relating Scaffold Architecture To Thermal Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Some authors also use SEM images for observations of scaffold anisotropy, but these are rarely quantitative. 45,46 Alternatively, a three-dimensional (3D) set of images may be obtained by a tomographic technique: most commonly X-ray microcomputed tomography (micro-CT) or magnetic resonance imaging (MRI). These techniques can be advantageous because they are non-destructive and involve no sample deformation in preparation, and can be used to measure SAV, pore volume and connectivity parameters.…”
Section: Existing Characterisation Techniquesmentioning
confidence: 99%